Integrating Legal Literacy into English Language Education Empowering University Students in the Global Era - Ismail, Nathasa Al Maidah (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
In today’s global era, students need more than just good English language skills. They also need to understand basic legal knowledge to help them become responsible and informed citizens. English language skills also broaden their career paths. This study examines how legal topics, such as human rights, employment law, and online safety, can be integrated into English language learning. By combining English lessons with simple legal content, students can improve their language skills while also learning about important real-world issues. This approach helps students think critically, speak confidently, and prepare themselves for life and work in a global society. This study used a qualitative method by analyzing teaching materials and interviewing English teachers and students at the university level. The results showed that students became more interested and active when English lessons were linked to legal topics that they could understand.